Hubungan Self Efficacy dengan Motivasi Berprestasi Siswa SMA - Suryani, Leli Teti; Sano, Afrizal (Lembaga Yasin AlSys, 2025)
This research is motivated by the fact that there are still many students who have low achievement motivation. This research aims to: (1) Describe the level of self-efficacy of students at SMAN 1 Banuhampu, (2) Describe the achievement motivation of students at SMAN 1 Banuhampu, (3) Test whether there is a significant relationship between self-efficacy and the achievement motivation of students at SMAN 1 Banuhampu . The research method used in this study is quantitative with a descriptive correlational approach. The sample of this study was 271 students selected using the stratified random sampling technique. The instruments used in this study were the self-efficacy instrument and the achievement motivation instrument. The data was processed using statistical techniques to determine the percentage value processed in the Microsoft Excel program, to find the relationship between the two variables the Pearson product moment technique was used. The results of the study showed that: (1) Self-efficacy in students at SMAN 1 Banuhampu as a whole was in the moderate category (53.16%). This means that most students at SMAN 1 Banuhampu are not yet confident in their abilities. (2) Achievement motivation in students of SMAN 1 Banuhampu as a whole is in the moderate category (61.88%) this means that most students already have motivation to achieve achievements. (3) There is a significant positive relationship between self-efficacy and achievement motivation in students of SMAN 1 Banuhampu with a correlation coefficient of 0.432 and a significance level of 0.000, where the higher the student's self-efficacy, the higher the achievement motivation in students, and vice versa, the lower the student's self-efficacy, the lower the achievement motivation in students.